Vaginal delivery in women with a low‐lying placenta: a systematic review and meta‐analysis. (10th March 2019) - Jansen, CHJR; de Mooij, YM; Blomaard, CM; Derks, JB; van Leeuwen, E; Limpens, J; Schuit, E; Mol, BW; Pajkrt, E
Abstract : Background: Low‐lying placentas are positioned close to the internal os of the cervix. The preferred way of delivery within this group is unclear. Objectives: To review the literature on the success of a vaginal delivery with a low‐lying placenta. Search strategy: We searched OVID EMBASE and MEDLINE for studies on vaginal delivery with a low‐lying placenta. Data collection and analyses: Data was extracted on successful vaginal delivery and emergency caesarean section due to haemorrhage. We distinguished between different distances between the cervical os and the placenta (internal os distance, IOD); 0–10, 11–20, and >20 mm. A meta‐analysis of proportions was made for successful vaginal delivery and emergency caesarean section at every cut‐off value. Maternal morbidity (i.e. antepartum blood loss, postpartum haemorrhage and blood transfusion) at different cut‐off values was evaluated. Main results: Of the 999 articles retrieved, 10 articles met our inclusion criteria. A vaginal delivery was successful at an IOD of 0–10 mm in 43%, at an IOD of 11–20 mm in 85%, and at an IOD of >20 mm in 82%. A shorter IOD had a higher chance of antepartum haemorrhage, whereas a larger IOD needed postpartum blood transfusion more often. Postpartum haemorrhage did not depend on IOD. Conclusion: A low‐lying placenta is not a contraindication for a trial of labour, and the morbidity in these women is not increased. However, women with a low‐lying placenta have a higher chance of an emergency caesarean section compared with women with a placenta outside the lower uterine segment. Therefore, shared decision‐making is mandatory in case of a trial of labour. Tweetable abstract: This systematic review demonstrates the possibility of a vaginal delivery in women with a low‐lying placenta within 20 mm of the cervix. Tweetable abstract: This systematic review demonstrates the possibility of a vaginal delivery in women with a low‐lying placenta within 20 mm of the cervix.